PENERAPAN SISTEM DALAM PEMBUATAN LAPORAN KEUANGAN PADA BADAN KESWADAYAAN MASYARAKAT (DESA KAJEKSAN, SIDOARJO, JAWA TIMUR) - Laely Aghe Africa; Dian Oktarina; Agustinus Kismet Nugroho Jati (-)
The problem of partners in the Community Self-Reliance Agency, in the Village of Kajeksan, Sidoarjo, East Java, is that there are no structured financial reports that are in accordance with accounting standards. In order to help solve the problem, the planned activity that will be carried out is to provide assistance to the partners of the Community Self-Reliance Agency, in the Village of Kajeksan Sidoarjo, East Java, by increasing financial management capabilities. The final result to be achieved in this Community Service activity is the existence of Standard Operating Procedures and the existence of the ability of village officials to use and apply a system-based Financial Statement. Based on the activities we have carried out both offline and online, the final conclusion is that partners have periodically applied structured financial statements both manually and systemically. While other output from this activity are publications in the National Journal.